2016
DOI: 10.1021/acs.inorgchem.6b01771
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Perfluoroaryldiselenadiazolyl Radicals: Insights into Dithiadiazolyl Chemistry

Abstract: The synthesis and structural characterization of a series of perfluoroaryldiselenadiazolyls [DSeDA; p-XCFCNSeSeN (X = F, Cl, Br, CF, NO, and CN for 2a-2f, respectively)] are described. Concentration-dependent solution UV/vis measurements on 2a follow the Beer-Lambert law and the transitions assigned through time-dependent density functional theory (TD-DFT) studies, indicating little propensity for dimerization in solution (10-10 M). Solution electron paramagnetic resonance (EPR) spectra reveal that these radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 79 publications
3
34
0
Order By: Relevance
“…The solid‐state structures of DTDA radicals are typically dictated by a combination of π* ··· π* dimers (a multi‐centre covalent bonding interaction) in which computational studies have shown dispersion plays a significant contribution , . In solution the dimerisation enthalpy has been estimated at 35 kJ mol –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid‐state structures of DTDA radicals are typically dictated by a combination of π* ··· π* dimers (a multi‐centre covalent bonding interaction) in which computational studies have shown dispersion plays a significant contribution , . In solution the dimerisation enthalpy has been estimated at 35 kJ mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most DTDA radicals dimerise in the solid state through what is considered to be a SOMO‐SOMO bonding interaction, sometimes referred to as “pancake bonding”, resulting in diamagnetic dimers (Scheme ). Computational studies indicate that dispersion plays a significant role in stabilising these π*–π* dimers , . DTDA radicals have been employed as building blocks for molecular conductors, magnets,, photoconductors, as paramagnetic ligands in coordination chemistry and, in the presence of a fluorophore, as multifunctional materials .…”
Section: Introductionmentioning
confidence: 99%
“…Thes tructure of 6 is structurally similar to 5 with intradimer Se···Se contacts at 3.1330(8) and 3.1895 (7) , shorter than the symmetric 3.197(2) observed in pristine [C 6 F 5 CNSeSeN] 2 . [21] There is then as et of four close Se···O contacts (Figure 8(bottom)) in the range 2.897(5)-3.348(4) , mean 3.136 .D issolution of 6 in CH 2 Cl 2 afforded an EPR spectrum consistent with am ixture of C 6 F 5 CNSeSeN and TEMPO radicals ( Figure S5.4.3).…”
Section: Zuschriftenmentioning
confidence: 93%
“…Thes imilarity in structure of many DTDAa nd DSDA radicals [21] prompted us to co-crystallize TEMPO with the diselenadiazolyl radical, [C 6 F 5 CNSeSeN] 2 .U sing as imilar methodology crystals of 6 were generated by vacuum sublimation. Thes tructure of 6 is structurally similar to 5 with intradimer Se···Se contacts at 3.1330(8) and 3.1895 (7) , shorter than the symmetric 3.197(2) observed in pristine [C 6 F 5 CNSeSeN] 2 .…”
Section: Zuschriftenmentioning
confidence: 99%
“…It has been reportedt hat the M05-2X functional is suitable for the description of long multicenter bonds of phenalenylr adical dimers and other hydrocarbons. [32,33] It is known that dispersion correction is significant for radical dimers [34,35] andt he M05-2Xf unctional does not include the dispersion correction terms. Also, it has been reported that M05-2X with D3 dispersion correction is over-parameterized, not affording results as good as in ap henalenylr adical dimer.…”
mentioning
confidence: 99%